2017
DOI: 10.1080/17429145.2017.1293852
|View full text |Cite
|
Sign up to set email alerts
|

Effects of PEG-induced drought stress on regulation of indole alkaloid biosynthesis in Catharanthus roseus

Abstract: Catharanthus roseus (C. roseus) plants were used to investigate the terpenoid indole alkaloids (TIAs) accumulation under the condition of PEG-induced drought stress. Multivariate analysis showed that 35% PEG6000 could induce more obvious and stable accumulation on proline (PRO) content and the relative water content (RWC). The results indicated that there were gradual increase and then decrease (p < .05) in the contents of vindoline (VIN) and catharanthine (CAT) under 35% PEG6000 stress, but the content of vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…In contrast to our results, Liu et al [73] demonstrated an increased accumulation of alkaloids and the expression of genes regulating secondary metabolite accumulation in drought-stressed C. roseus. However, reports discussing the combined effects of drought and heat stress on the accumulation of secondary metabolites are rare.…”
Section: Effects Of Drought and Heat Stress On The Growth And Physiolcontrasting
confidence: 99%
“…In contrast to our results, Liu et al [73] demonstrated an increased accumulation of alkaloids and the expression of genes regulating secondary metabolite accumulation in drought-stressed C. roseus. However, reports discussing the combined effects of drought and heat stress on the accumulation of secondary metabolites are rare.…”
Section: Effects Of Drought and Heat Stress On The Growth And Physiolcontrasting
confidence: 99%
“…Drought has been shown to cause dynamic variations in the levels of vindoline and catharanthine, wherein vindoline displayed a decline-rise trend while catharanthine showed a gradual decline in its levels in C . roseus tissues subjected to PEG-induced drought stress 81 . Geraniol content was found to decrease upon drought treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaloids accumulation recorded following stressful Co 2+ treatments is a defense response against oxidative stress (13). It was recorded in C. roseous following exposure to different types of stress including heavy metals (14)(15)(16)(17), drought (53) and fungal attack (54).…”
Section: Discussionmentioning
confidence: 99%